The Impact of Developer Experience in Using Java Cryptography - Hazhirpasand, Mohammadreza; Ghafari, Mohammad; Krüger, Stefan; Bodden, Eric; Nierstrasz, Oskar (2019 ACM/IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM))

AuthCheck: Program-state Analysis for Access-control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (10th Workshop on Tools for Automatic Program Analysis (TAPAS))

Explaining Static Analysis -- A Perspective - Nachtigall, Marcus; Nguyen Quang Do, Lisa; Bodden, Eric (1st International Workshop on Explainable Software (EXPLAIN) at ASE)

A Qualitative Analysis of Android Taint-Analysis Results - Luo, Linghui; Bodden, Eric; Späth, Johannes (IEEE/ACM International Conference on Automated Software Engineering (ASE 2019))

SWAN_ASSIST: Semi-Automated Detection of Code-Specific, Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Johnson, Oshando; Bodden, Eric (IEEE/ACM International Conference on Automated Software Engineering (ASE 2019), Tool Demo Track)

CrySL: An Extensible Approach to Validating the Correct Usage of Cryptographic APIs - Krüger, Stefan; Späth, Johannes; Ali, Karim; Bodden, Eric; Mezini, Mira (IEEE Transactions on Software Engineering)
Keywords: Java; Encryption; Static analysis; Tools; Ciphers; Semantics; cryptography; domain-specific language; static analysis

Codebase-Adaptive Detection of Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Bodden, Eric (ACM SIGSOFT International Symposium on Software Testing and Analysis (ISSTA))

MagpieBridge: A General Approach to Integrating Static Analyses into IDEs and Editors - Luo, Linghui; Dolby, Julian; Bodden, Eric (European Conference on Object-Oriented Programming (ECOOP))

Synchronized Pushdown Systems for Pointer and Data-Flow Analysis - Späth, Johannes

Codebase-Adaptive Detection of Security-Relevant Methods - Piskachev, Goran; Nguyen, Lisa; Bodden, Eric

ACMiner: Extraction and Analysis of Authorization Checks in Android's Middleware - Albert Gorski Iii, Sigmund; Andow, Benjamin; Nadkarni, Adwait; Manandhar, Sunil; Enck, William; Bodden, Eric; Bartel, Alexandre (ACM Conference on Data and Application Security and Privacy (CODASPY 2019))
Keywords: ITSECWEBSITE; CROSSING

Context-, Flow-, and Field-sensitive Data-flow Analysis Using Synchronized Pushdown Systems - Späth, Johannes; Ali, Karim; Bodden, Eric (Proceedings of the ACM SIGPLAN Symposium on Principles of Programming Languages)
Keywords: ATTRACT; ITSECWEBSITE; CROSSING

Analyse und Vorhersage rezeptur- und zeitabhängiger Enthaftungserscheinungen geklebter SMC-Bauteile - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson (19. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analysis of formulation- and aging-dependent failure phenomena of bonded Sheet Molding Compounds (SMC) - Aßmuth, Verena; Teutenberg, Dominik; Meschut, Gerson

Effects of different visual conditions on standing balance in a virtual reality scene: a pilot study - Vogt, S; Neuhaus, D; Baumeister, Jochen (Sportmotorik 2019. Adaptation, Lernen und virtuelle Welten)

Effects of an augmented reality training using a myoelectric hand prosthesis: a pilot study - Neuhaus, D; Vogt, S; Boschmann, A; Dosen, S; Baumeister, Jochen (Sportmotorik 2019. Adaptation, Lernen und virtuelle Welten)

A preliminary prospective Analysis of electrocortical signatures underlying ACL injury - Bonnette, S; Diekfuss, JA; Barber Foss, KD; DiCesare, CA; Riley, MA; Riehm, C; Moore, C; Grooms, DR; Myer, GD; Baumeister, Jochen

Muscle activity patterns in imitation ski jumps - Claussen, L; Baumeister, Jochen; Braaten, S; Ettema, G (Book of abstracts - German Exercise Science and Training conference)

Effect of age on reactive multidirectional speed in highly trained youth soccer players - Büchel, D; Lehmann, T; Baumeister, Jochen (Book of abstracts - German Exercise Science and Training conference)

Sports-specific differences in reactive multidirectional speed in tema sports athletes using the Speedcourt - Büchel, D; Döring, M; Berkel, F; Baumeister, Jochen (Book of abstracts - German Exercise Science and Training conference)

Untersuchungen zu kontinuums- und bruchmechanischen Methoden für die Prognose des Crashverhaltens toleranzbehafteter Strukturklebverbindungen - Bobbert, Mathias

Paying for Performance in Private Equity: Evidence from Venture Capital Partnerships - Hüther, Niklas; Robinson, David T.; Sievers, Sönke; Hartmann-Wendels, Thomas (Management Science (VHB-JOURQUAL 3 Ranking A+))
We offer the first empirical analysis connecting the timing of general partner (GP) compensation to private equity fund performance. Using detailed information on limited partnership agreements between private equity limited and general partners, we find that “GP-friendly” contracts—agreements that pay general partners on a deal-by-deal basis instead of withholding carried interest until a benchmark return has been earned—are associated with higher returns, both gross and net of fees. This is robust to measures of performance persistence, time period effects, and other contract terms and is related to exit-timing incentives. Timing practices balance GP incentives against limited partner downside protection.
Keywords: venture capital; compensation; private equity; VC partnership; pay-performance relation

ELOBEV - Erforschung von elektrolytischen Beschichtungssystemen für Verbindungselemente aus höchstfesten Werkstoffen - Bangel, Martin; Neubauer, Michael; Kuhlmann, Matthias; Rossel, Moritz Sebastian; Klostermann, Heidrun; Rablbauer, Ralf; Weber, Marius (Projektband der BMBF-Förderinitiative Innovative Elektrochemie mit neuen Materialien – InnoEMat)

Coaching on the Job bei Unternehmen des Maschinen- und Anlagenbaus - Wissenslücken schließen zur Weiterpflege modernisierter IT-Anwendungen - Fazal-Baqaie, Masud; Strüwer, Jan-Niclas; Schmelter, David; Dziwok, Stefan (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Improvement of Software Requirements Quality based on Systems Engineering - Holtmann, Jörg

Component-Based Refinement and Verification of Information-Flow Security Policies for Cyber-Physical Microservice Architectures - Gerking, Christopher; Schubert, David (International Conference on Software Architecture (ICSA 2019))

Application-aware Intrusion Detection: A Systematic Literature Review and Implications for Automotive Systems - Schubert, David; Eikerling, Hendrik; Holtmann, Jörg (17th escar Europe : embedded security in cars)

Monitoring and Control of Production Processes based on Key Performance Indicators for Mechatronic Systems - Wohlers, Benedict; Dziwok, Stefan; Pasic, Faruk; Lipsmeier, Andre; Becker, Matthias (International Journal of Production Economics)
The processes for manufacturing and operating modern technical products require expertise in multiple disciplines like mechanical engineer-ing, electrical engineering, and software engineering. Assessing the current condition and quality of these processes and the machines in-volved is challenging due to the inherent complexity of the products and the required expertise in multiple engineering domains. Globaliza-tion and increasing competition make it necessary to reduce production costs while at the same time ensuring high throughput and product quality. Without the ability to precisely assess the condition and quality of production processes and involved machines, taking action to steer these metrics is nearly impossible and results in unnecessary high production costs. In our previous publications, we introduced the concept of Key Performance Indicators (KPIs) for mechatronic systems as a concept to assess the condition and quality of products and production processes in a graspable yet substantial and efficient way. In this paper, we further refine our KPI concepts und evaluate them for two different use cases: we apply our KPI concept to a manufacturing process in the mechatronic system domain and an operation process in the food production domain. We provide detailed insights in how we applied our concepts within these domains and report about lessons learned. In addition, we provide a business case estimation for our soft-ware solution that assesses the KPIs of our food production domain example.

Inverse optimal control problem: the linear-quadratic case - Jean, Frederic; Maslovskaya, Sofya (2018 IEEE Conference on Decision and Control (CDC))

On projective and affine equivalence of sub-Riemannian metrics - Jean, Frédéric; Maslovskaya, Sofya; Zelenko, Igor (Geometriae Dedicata)

Charakterisierung und Modellierung von Kerbeffekten durch Mischverbindungen in Karosseriebauteilen aus höchstfesten Stählen - Unruh, Eduard; Hein, David; Meschut, Gerson; Bähr, Philipp; Sommer, Silke (9. Fügetechnisches Gemeinschaftskolloquium)

Analytische Auslegung der Schwingfestigkeit geclinchter Verbindungen - Unruh, Eduard; Hein, David; Meschut, Gerson (9. Fügetechnisches Gemeinschaftskolloquium)

Downturns Are a Better Time For Deal Hunting - Sievers, Sönke; Kengelbach, Jens; Keienburg, Georg; Bader, Maximilian; Degen, Dominik; Gell, Jeff; Nielsen, Jesper

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Spray coating of poly(acrylic acid)/ZnO tetrapod adhesion promoting nanocomposite films for polymer laminates - Meinderink, Dennis; Nolkemper, Karlo J.R.; Bürger, Julius; Orive, Alejandro G.; Lindner, Jörg K.N.; Grundmeier, Guido (Surface and Coatings Technology)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)

Konstruktive Gestaltung geklebter FVK-Mischverbindungen unter Berücksichtung von Randeffekten - Göddecke, Johannes; Meschut, Gerson; Teutenberg, Dominik

Uniform approximation in classical weak convergence theory - Bengs, Viktor; Holzmann, Hajo (arXiv:1903.09864)
A common statistical task lies in showing asymptotic normality of certain statistics. In many of these situations, classical textbook results on weak convergence theory suffice for the problem at hand. However, there are quite some scenarios where stronger results are needed in order to establish an asymptotic normal approximation uniformly over a family of probability measures. In this note we collect some results in this direction. We restrict ourselves to weak convergence in $\mathbb R^d$ with continuous limit measures.

Success Factors for the Consolidation and Anchoring of Digitalisation Projects - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Strategies Beyond Borders – Transforming Higher Education in a Digital Age. Book of Abstracts)

Digitalisierungsstrategien auf dem Prüfstand – eine empirische Untersuchung auf Basis der Grounded-Theory-Methodologie an deutschen Hochschulen - Graf-Schlattmann, Marcel; Meister, Dorothee M.; Oevel, Gudrun; Wilde, Melanie (Teilhabe in der digitalen Bildungswelt)

Entwicklung von Optimierungsstrategien für Strukturbauteile unter Ausnutzung der Potentiale des Laser-Strahlschmelzens - Brüggemann, J.P.; Risse, L.; Kullmer, G.; Richard, H.A. (Additive Fertigung von Bauteilen und Strukturen – Neue Erkenntnisse und Praxisbeispiele)

Einsatz ingenieurmäßiger Methoden zur Lösung chirurgischer Herausforderungen - Risse, L.; Woodcock, S.C.; Kullmer, G.; Schramm, B.; Richard, H.A.

Möglichkeiten additiver Fertigungsverfahren im Zuge der Digitalisierung für den Planungsprozess chirurgischer Eingriffe - Risse, L.; Schramm, B. (DVM - Bericht 1685, DVM-Tag 2019 – Bauteil verstehen)

Einflussfaktoren auf Bauteilgüte lasergeschmolzener Strukturen - Brüggemann, J.P.; Risse, L.; Richard, H.A.; Kullmer, G. (DVM - Bericht 251, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Bewertung von verschieden gearteten Gitterstrukturen in Bezug auf ihre Einsatzfähigkeit in Bandscheibenimplantaten - Woodcock, S.C.; Risse, L.; Kullmer, G.; Richard, H.A. (DVM - Bericht 404, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Einflussfaktoren auf Bauteilgüte lasergeschmolzener Strukturen - Brüggemann, J.P.; Risse, L.; Richard, H.A.; Kullmer, G. (DVM-Bericht 251, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Potentiale des Einsatzes individueller, additiv gefertigter medizinischer Hilfsmittel - Risse, L.; Woodcock, S.C.; Kullmer, G.; Schramm, B.; Schlenker, F.; Richard, H.A. (DVM-Bericht 404, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen)

Strukturoptimierung durch den Einsatz des Laser-Strahlschmelzprozesses zur realitätsnäheren Erfassung von Fahrzeug-Lastdaten - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Duffe, T.; Neumann, J.; Vidner, J.; Kullmer, G.; Richard, H.A. (DVM-Bericht 404, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Reconstruction of a defective finger joint surface and development of an adapted external fixator - Risse, L.; Woodcock, S.C.; Kullmer, G.; Schramm, B.; Richard, H.A. (Lecture Notes in Computational Vision and Biomechanics)

Methodik zur Qualifizierung des Lasersinter Prozesses für die Serienfertigung - Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 16th Rapid.Tech Conference)
Zuverlässige, wiederholbare Bauteileigenschaften sind unabdingbar um das Herstellungsverfahren Polymer Lasersintern im industriellen Prozess-Portfolio vieler Firmen aufnehmen zu können. Einige Unternehmen und Institute haben sich daher in jüngster Zeit mit dem Thema der reproduzierbaren Bauteileigenschaften beschäftigt. Mit der hier vorgestellten und angewandten Methodik wird nicht nur der Prozessablauf vom Bauteil bis zu Nachbearbeitung betrachtet, sondern auch die Maschinenperformance in einem Ringversuch und über einen längeren Zeitraum geprüft. Rückgrat dieser Untersuchung bildet hierbei der aus der Six Sigma Lehre stammende DMAIC (Define - Measure - Analyse - Improve - Control) Verbesserungszyklus. Hierfür wird ein Standard-Prozess definiert. Diesem folgend werden die für die Industrie oder den Anwender interessanten Messungen aufgenommen und analysiert. Anschließend wird der Prozess sowie die Messmethodik optimiert und auch Kontrollmethoden definiert. Für die Anwendung der entwickelten Methodik wird exemplarisch der Maschinentyp EOS P396 mit PA2200 untersucht. Daten für die Bestimmung der Mechanik, der Optik und der Haptik sowie für die Dimensionen und die Bauteildichte werden als Qualitätskriterium aufgenommen und über einen längeren Zeitraum analysiert. Weiteres Ziel ist es, den Messaufwand zu reduzieren und die Qualitätssicherung im Serienbtrieb zu gewährleisten.